Análise do perfil de liderança atual e ideal de treinadores de futsal de alto rendimento, através da Escola de Liderança no Desporto (ELD) - Varley Teoldo da Costa (2003)
As in other competitive sports, high-level Futsal coaches play an important role in conducting their teams in tournaments and games. There are a very few studies discussing the leadership style of coaches assessed through self-perception. The majority of the studies in Futsal are focused in the technical, tactical and physical aspects. The purposes of the present study were to evaluate and compare the selfperception of Futsal coaches with different experience levels, in relation to their real and ideal behavior, to verify the internal consistency of the Sport Leadership Scale (LSS) in the Brazilian Portuguese language. The Real and the Ideal versions of the LSS, each composed of 40 situations were used. Additionally, the participants provided personal and professional information, which was also used in the analysis. They were 50 high level coaches who participated in the Brazilian National Futsal League, in the Brazilian Junior Championship of State Teams and in the State and Metropolitan Championship of Minas Gerais. The coaches mean age was 35.82 years (± 8.39) and had been coaching for 9.82 years (± 7.50) at the time of the study. The internal consistency (Alpha Cronbach) were within acceptable levels for both versions; the Ideal version (0.76) and for the Real version (0.85). It was conclude that the coaches, according to the Real version, see themselves as democratic leaders (x=2,17) who adopt a training-instruction style (x=3,44), and believe that the ideal leader (LSS-ldeal) will should a coach that conduct their teams using the democratic way (x=2,29) and the training-instruction style (x=3,58). There were no differences in LSS for coaches with different levels of experience.